The Coercive Edge of Kindness: A Critical Analysis of 'Random Acts' in Nursing - Jackson, Debra; Bond, Carmel; McCormack, Brendan; Watson, Adrianna; Wilson, Denise; Cleary, Michelle (Wiley, 2026)
Kindness is frequently framed as an unassailable virtue, celebrated across social, professional and political domains as a simple and uncomplicated good. It is rarely problematised, and its assumed benefits are seldom interrogated, leaving kindness largely positioned as a self-evident moral imperative. In this paper, we adopt a Foucauldian lens, not to seek an essential definition of kindness, but to consider how it circulates and operates discursively, what effects it produces and what is surrendered in its performance. We position kindness as a discourse that does not merely encourage compassion or generosity but also regulate behaviour, shapes subjectivities and establishes boundaries around what may or may not be said. Through such mechanisms, the imperative to 'be kind' can act to silence resistance, temper critique and foster compliance, functioning as a subtle technology of governance. By problematising kindness in this way, we reveal how a practice so often presented as wholly benevolent can also operate as a powerful disciplinary force. We suggest that alternatives to the disciplinary framing of kindness may be found within First Nations knowledge systems, which offer different ways of understanding generosity and care beyond Western institutional logics. Our purpose is not to argue for the abandonment of kindness, but to highlight that it should not be accepted uncritically; its operations and consequences must be understood in order for it to be engaged ethically and politically.
Keywords: critical analysis; cultural perspectives; discourse; kindness; 1110 Nursing; Nursing; 4204 Midwifery; 4205 Nursing; Humans; Coercion; Empathy